Comparing the efficacy of unilateral biportal endoscopic transforaminal lumbar interbody fusion and minimally invasive transforaminal lumbar interbody fusion in lumbar degenerative diseases: a systematic review and meta-analysis - Haopeng Luan; Cong Peng; Kai Liu; Xinghua Song (Journal of Orthopaedic Surgery and Research, 2023)
Abstract Objective To compare the efficacy and safety of unilateral biportal endoscopic transforaminal lumbar interbody fusion (BE-TLIF) and minimally invasive transforaminal lumbar interbody fusion (MIS-TLIF) in lumbar degenerative diseases. Methods This study was registered on International Prospective Register of Systematic Reviews (PROSPERO) (ID: CRD42023432460). We searched PubMed, Embase, Web of Science, Cochrane Library, China National Knowledge Infrastructure, Wan Fang Database, and Wei Pu Database by computer to collect controlled clinical studies on the efficacy and safety of unilateral BE-TLIF and MIS-TLIF in lumbar degenerative diseases from database establishment to May 2023. Two researchers screened the literature, extracted data and evaluated the risk of bias of the included studies, recorded the authors, and sample size, and extracted the intraoperative blood loss, operation time, postoperative drainage, Oswestry disability index, Visual analogue scale, lumbar lordosis, disk height, hospital length stay, fusion rate, and complications in each study. Meta-analysis was performed using Revman 5.4 software provided by Cochrane Library. Results A total of 14 cohort studies with a total of 1007 patients were included in this study, including 472 patients in the BE-TLIF group and 535 patients in the MIS-TLIF group. The BE-TLIF group had lower intraoperative blood loss than the MIS-TLIF group [mean difference (MD) = − 78.72, 95% CI (− 98.47, − 58.97), P < 0.00001] and significantly reduced postoperative drainage than the MIS-TLIF group [MD = − 43.20, 95% CI (− 56.57, − 29.83), P < 0.00001], and the operation time was longer than that of the MIS-TLIF group [MD = 22.68, 95% CI (12.03, 33.33), P < 0.0001]. Hospital length stay in BE-TLIF group was significantly less than that in MIS-TLIF group [MD = − 1.20, 95% CI (− 1.82, − 0.57), P = 0.0002]. Conclusion Compared with MIS-TLIF, BE-TLIF for lumbar degenerative diseases has the advantages of less intraoperative blood loss, less early postoperative low back and leg pain, shorter postoperative hospital length stay, and faster early functional recovery.